NATIONAL ASSEMBLY OF THE REPUBLIC OF SERBIA AND GERMAN BUNDESTAG - COMPARATIVE ANALYSIS - Toroman, Aleksandra (Glasnik Advokatske komore Vojvodine, 2022)
The Bundestag, as the legislative body of the Federal Republic of Germany, is its most important body. On the other hand, the National Assembly in the Republic of Serbia has a significant influence and role. Since the legislative bodies represent the people and the people are the bearers of the sovereignty of a state, which does not exercise its power directly but through the work and functioning of the parliament, the legislative bodies provide the supreme power in some states. In this sense, the aim of the legal research and analysis in this paper is a parallel overview of the functioning of legislative bodies and an account of the influence of these bodies in their countries. Moreover, each organ has its own particular characteristics that distinguish it from others. Therefore, the purpose of this paper is to highlight the distinctive features of both legislative bodies as well as their commonalities.